Socialization of Benefits and Management Training in Village-Owned Enterprises as an Effort to Improve Community Welfare in Pamijahan District, Bogor Regency - Patiro, Shine Pintor Siolemba; Damayanti, Prisila; Hendrian, Hendrian; Rekarti, Endi; Mubarok, Faizul; Widokarti, Joko Rizkie; Lumbangaol, Lasando (Unram Journal of Community Service, 2025)
This Community Service (PkM) activity was carried out in Paminjahan District, Bogor Regency, with the target of RT/RW, Hamlet Head, Village BPD, village government officials, and Village-Owned Enterprises (BUMDes) Management. The business actors involved are those who have businesses in the field of trade and services. This PkM activity was carried out to provide public and business actors with an understanding of the legality, goals, and benefits of BUMDes for increasing development and improving the welfare and prosperity of the community fairly and equitably. Through an increase in Village Original Income (PADes) income, business activities are expected to continue to develop by paying attention to and implementing supporting factors for business activities. Thus, the PkM activities held include socializing about the legality, goals, and benefits of BUMDes and socializing about professional human resource management in managing BUMDes in the village. The socialization was adjusted to the problems and needs faced by BUMdes administrators in Paminjahan District, Bogor Regency. The method of implementing the activity consists of three stages. First, the preparation stage includes pre-survey, team formation, making and submitting proposals, coordinating teams and partners, and preparing training tools and materials. The second stage is the program implementation stage in the form of socialization. Socialization is carried out through counseling (material presentation) and discussion. The third stage is the evaluation and reporting stage. The evaluation was carried out by comparing the conditions of partners before and after the program's implementation with interview and observation methods. After that, a report was prepared for further publication. The material presented in the socialization was in the form of the Legality of BUMDes, as well as the benefits and goals of BUMDes towards increasing development and prosperity for all communities in the village. Based on the results of the implementation, the objectives of this implementation can be broadly achieved, which is shown through the improvement of the value order of society in the field of education, especially in economics.